Typing of Brucella field strains isolated from livestock populations in Italy between 2001 and 2006 - Elisabetta Di Giannatale; Fabrizio De Massis; Massimo Ancora; Katiuscia Zilli; Alessandra Alessiani (Veterinaria Italiana, 2008)
The identification of species and biovars of Brucella field strains isolated in outbreaks is essential to fully understand the epidemiology of the disease and to trace sources of infection, thereby improving the outcome of brucellosis eradication programmes. It is important to identify the presence of Brucella strains in livestock populations and to determine the presence of new strains that might previously have been considered exotic. In this study, 732 Brucella strains isolated from livestock were submitted for typing by the Italian Istituti Zooprofilattici Sperimentali to the National Reference Laboratory for brucellosis between 2001 and 2006. Animal species affected, biovars typed and spatial distribution of isolates are discussed. Brucella field strains were identified using both conventional bacteriological methods and molecular techniques. Species identification was performed using the AMOS (AbortusMelitensisOvisSuis)-polymerase chain reaction. For biovar identification, amplification of omp2a, omp2b and omp31 genes was performed, followed by restriction fragment length polymorphism. Final biovar identification was performed by growth in the presence of basic fuchsin and thionin, using the slide agglutination test with Brucella A- and M- specific antisera.